The Date of Maturity and its Effect on the Contract of Sale in the Islamic Jurisprudence - Fawaz Mhmoud Muhammad Bsharat (My University, 2006)
I thank Allah, the god of all peace and prayers of Allah be upon the messenger of mercy to all and upon all this companion, and relation. I thank Allah who guided us to the straight path as we wouldn’t have been if he hadn’t. This research the late of Maturing and its effects on the selling contact in the Islamic jurisprudence is a thesis given as a fulfillment for M.A requirement in the Fiqh and jurisprudence department faculty of high studies at AL-Najah national university in Nablus. Also I thank my supervisor eminence Dr. Jamal Ahmed Za'ed Al- Kilane. The these is includes three sections, an introduction and a conclusion The introduction talks about tow method of research, information gatherings, documentation I t also talks about some of the difficulties I faced to the stage, at study and preparing as for as section are concerned, I divided every section into different chapter. Section one includes four chapters paying in installment type selling Paying in advance chain selling, I give definitions legitimacy The different points of the view and any suggestion in this respect. The second section in about the effects of the date of maturity on the commodity it include three chapters: selling in debt. Deal contract. cash contract. I also give definition show legitimacy and any rules related to every chapter in addition to any suggestion. related to every case. The third section is the date of maturity effects on beneficiary selling it talks about the permission to make beneficiary selling; I give definition, legitimacy rules and suggestions. In the conclusion, I wrote down the conclusions I reached in addition to my recommendations that could help in setting down people financial problems.

الحمد لله رب العالمين، والصلاة والسلام على المبعوث رحمة للعالمين، وعلى آله وصحبه أجمعين. الحمد لله الذي هدانا لهذا وما كنا لنهتدي لولا أن هدانا الله وبعد: فهذا البحث والذي يحمل عنوان "الأجل وأثره في عقد البيع في الفقه الإسلامي" هو عبارة عن رسالة (أطروحة) قدمت استكما ً لا لمتطلبات درجة الماجستير في الفقه والتشريع بكلية الدراسات العليا في جامعة النجاح الوطنية في نابلس، وتفضل بقبول الإشراف عليها فضيلة الدكتور جمال أحمد زيد الكيلاني حفظه الله ورعاه. وقد جاءت في ثلاثة فصول ومقدمة وخاتمة، تكلمت في المقدمة عن منهجي في البحث من حيث جمع المعلومات، وتوثيقها، والترتيب والتنسيق الذي اعتمدته فيها، كما أشرت إلى بعض الصعوبات التي واجهتني في مرحلَتيْ الدراسة والإعداد. أما بالنسبة للفصول فقد أعطيت كل فصل اسمًا وفيه عدة مباحث، فالفصل الأول. "أثر الأجل في الثمن" وفيه أربعة مباحث: بيع التقسيط، و بيع العينة، و بيع العربون، و بيع حبل الحبلة. فذكرت تعريفه الشرعي واللغوي، ومشروعيتها، وآراء العلماء فيها من حيث الصحة والفساد، وذيلت لكل مبحث القرارات الفقهية المتعلقة بها، المنبثقة عن المجمع الفقهي وذلك زيادة في الإثراء. أما الفصل الثاني فهو بعنوان: "أثر الأجل في السلعة" و فيه ثلاثة مباحث: بيع الدين، وعقد السلم، و عقد الصرف. بينت في هذا الفصل تعريف كل مبحث ومشروعيته والأحكام المتعلقة به وأبرزت أثر الأجل في كل نوع منه، بالإضافة إلى القرارات الفقهية المتعلقة بكل مبحث. أما الفصل الثالث فهو بعنوان: "أثر الأجل في بيع المنافع" فهو يتحدث عن عقد الإجارة التي تسمى بيع المنافع، حيث بينت تعريفها ومشروعيتها والأحكام المتعلقة بها وبينت أثر الأجل فيها وشرط صحتها من حيث معلومية المدة. أما الخاتمة فقد دونت فيها أهم النتائج التي توصلت إليها بعد الدراسة والتحليل للموضوعات، بالإضافة إلى التوصيات التي تسهم في حل بعض مشكلات الناس التي توقعهم في الربا المحرم. هذه هي أهم وابرز القضايا التي تحدثت عنها في هذه الرسالة، أسأل الله أن يجعل ذلك في ميزان حسناتي، وان ينفعني بما علمني وان يعلمني ما ينفعني، انه هو السميع العليم.
أثر الأجل في عقد البيع في الفقه الإسلامي